O uso da gamificação como metodologia ativa no ensino de matemática - OLIVEIRA, Danylo da Silva (2022)
This research aimed to unsee the possibilities of using Gamification as an active methodology in the teaching of Mathematics. To develop it, the objective was to demonstrate that the elements of gamification applied in learning activities can provide increased engagement and motivation in educational activities. Starting from the analysis of the main authors on the concept of gamification and how its application has been observed in education, which justifies its in-depth research, in order to discover the best paths for its use. Participants in this study were 10 teachers from the municipal and state network, which was performed synchronously and asynchronously through the use of the Googleclassroom platform, and 42 students, belonging to the School of the Municipal Network of Acará Lydia Lima., who were submitted to practice through gamification workshops. The main results obtained in this article through observation, discussion and the questionnaire indicate that the participants of the gamificated discipline understood that teaching requires a reflective and participatory posture. The collected data indicate how much it was possible to understand that the teacher can use several strategies for the teaching exercise, in the search for the effectiveness of learning, and it was possible to verify that there are teachers who use the strategy without knowing its theoretical foundations, and through studies on gamification can improve their practices. Thus, it can be concluded that gamification can be a starting point for teachers who desire a differentiated way of teaching and engaging their students in a pleasurable, interesting and motivating study, thus making learning more meaningful.